THE PSYCHOLOGICAL PROFILE OF POLICE DRIVERS WORKING IN SECURITY POLICE - Barko, Vadym; Ostapovych, Volodymyr (PSYCHOLOGICAL JOURNAL, 2020)
The article examines psychological aspects of security police drivers’ professional work in the context of the implementation of their professional tasks. By theoretical analysis and generalization of scientific and methodological literature, observation, used questionnaires, performed psychological examination and mathematical statistics, we considered theoretical foundations of research on security police drivers’ professional work and requirements for their general and professional abilities. The performed extensive experimental study that involved about 300 police officers from different regions of the country allowed us to develop the psychological profile of a police driver’s profession. This psychological profile includes a set of characteristics that describe qualitatively and quantitatively drivers’ personality for further psychological examination. The psychological profile reveals a qualitative characteristic, the list and quantitative ranges for examined parameters characterizing a successful specialist, a professional in a particular field of professional work; such profile includes a person’s major psychological characteristics and is used in legal psychology to predict possible human actions and behavior. Security police drivers’ professional work is associated with a number of important tasks and imposes high demands on police officers’ individual psychological characteristics, as well as on their knowledge, skills and competencies. The article highlights the main professional requirements to police drivers’ general and special abilities, presents the requirements for their sensory-perceptual sphere, cognitive processes, communicative features and the most important individual psychological characteristics (character, temperament, etc.). Police drivers must have a high speed of simple reactions and reactions to a moving object; high accuracy and coordination of movements, the time of their sensorimotor reactions is important their work. The structure of police drivers’ motivation to professional work is revealed, as well as the results of expert evaluation of their most important professional qualities. The generalized psychogram of a police driver is presented in the form of the expanded table. The research results revealed the list of professionally important qualities that a security police driver must possess, as well as psychological contraindications to this profession. The obtained data can be used at professional psychological selection of police officers and their appointment to the positions of security police drivers.